2017
DOI: 10.5812/amh.63399
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 Gene Polymorphism and Breast Cancer

Abstract: Objectives: Estrogen is one of the important factors in the progression of breast cancer. Cytochrome P450 Superfamily (CYPs) plays an important role in the metabolism of estrogen. The CYP1A1 gene has been shown to be involved in the metabolism of estradiol. Several studies have reported a significant association between CYP1A1 polymorphisms and breast cancer. Methods:In the present work, the association between CYP1A1 polymorphism (Thr461Asn) and breast cancer in Guilan province was investigated. The blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…[29] Statistical analysis by logistic regression model showed no statistical relationship between M2 genotype and breast cancer risk ( P = 0.72 and OR = 0.84). Our results are in line with some previous reports in different population like Indian,[30] Danish,[31] and American,[32] and different Iranian ethnic like Gilaki[33] and Fars. [34] Their finding revealed that there is no correlation between polymorphism M2 of CYP1A1 gene and breast cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…[29] Statistical analysis by logistic regression model showed no statistical relationship between M2 genotype and breast cancer risk ( P = 0.72 and OR = 0.84). Our results are in line with some previous reports in different population like Indian,[30] Danish,[31] and American,[32] and different Iranian ethnic like Gilaki[33] and Fars. [34] Their finding revealed that there is no correlation between polymorphism M2 of CYP1A1 gene and breast cancer risk.…”
Section: Discussionsupporting
confidence: 93%